A study of inulinase production in Aspergillus niger using fractional factorial design - Poorna, V.; Kulkarni, P.R. (Bioresource technology, 1995)
The effects of process parameters on inulinase production by Aspergillus niger van Teighem have been studied by one-factor-at-a-time and fractional design. Use of various carbon sources, singly and in combination, suggested that inulinase production by Aspergillus niger van Teighem is probably inducible and subject to catabolite repression. A fractional factorial method using the Plackett-Burman design showed that inulin, among the various carbon sources studied, had the highest positive influence on inulinase production.